Meningkatkan Kemampuan Membaca Melalui Penerapan Pembelajaran Kooperatif Model Jigsaw pada Siswa Kelas IV SDN 2 Uebone - Harni, Harni (Jurnal Paedagogy, 2020)
One of the efforts to improve Indonesian language learning achievement for fourth grade students in elementary school is by applying the Jigsaw cooperative learning model. The purpose of this study is to determine whether there are differences in learning achievement between students whose learning uses the Jigsaw cooperative learning model. The study design used a pretest-posttest control group design experiment. The population is grade IV students of SDN 2 Uebone Bulan Ampana Tete District. The method of collecting data through tests, before the treatment of each group was given a pretest and after the treatment was given a posttest. From the results of the analysis prove that there are significant differences in the achievement of Indonesian language learning students who are taught using the Jigsaw Cooperative Learning model. There was also a significant difference in the learning achievement of students who were taught using the Jigsaw Cooperative Learning model. From the results of the analysis of this study it was concluded that the best learning model is the Jigsaw Cooperative Learning Model.